Effect of Company Performance on Sharia Commercial Bank Executive Compensation in Indonesia - Mahfud Asyari; Firna Hayyu Nindya Maritsa (EkBis: Jurnal Ekonomi dan Bisnis, 2020)
After the disclosure of data from companies, research on executive compensation began to develop. Several studies on executive compensation in banking found that the determination of compensation is positively related to company performance. This research aims to determine the relationship between company performance and executive compensation of Islamic Commercial Bank’s  in Indonesia. Company performance is proxied by Return on Assets (ROA). This study uses a sample of Islamic Commercial Banks because they have very good performance growth and currently only have a market share of 6.18% compared to the national financial market so they still have the potential to experience growth.  Furthermore, sample used 14 Islamic commercial banks registered with the OJK during 2014-2019. The research method used panel data regression analysis. The results showed that the performance of Islamic Commercial Bank’s has an effect on executive compensation. Islamic Commercial Bank Executives have an obligation to improve company performance (ROA) because it affects the compensation received by the executive.